The Pooh book of quotations : in which will be found some useful information and sustaining thoughts by Winnie-the-Pooh and his friends - Milne, A. A. (Alan Alexander), 1882-1956 (Dutton Children's Books, 1991)
A collection of quotations from the prose and poetry of A. A. Milne, with an emphasis on the Winnie-the-Pooh books, grouped by topics such as weather and food.